สงฆ์กับกิจกรรมการอนุรักษ์ภูมิทัศน์ป่าไม้: กรณีศึกษา พระราชวิสุทธิมุนี (หลวงพ่อเยื้อน ขฺนติพโล) พุทธอุทยานวัดเขาศาลา อำเภอบัวเชด จังหวัดสุรินทร์ - ไตรรัตน์วงศ์ นันทชัย (Asian Creative Architecture, Art and Design, 2018)
Abtract This research aimed to study the achievement on forest landscape conservation work by Phra Ratchawisutthimunee (Yearn Kantipalo), the monk at Khao Sala Buddhist Temple, in the province of Surin. From the data collection through the in-depth interviews and the empirical research, the finding revealed that Phra Ratchawisutthimunee conservation work’s method started from the most damaged area of the forest the from wood poachers then applied the landscape conservation activities from making reservoir, preventing forest fire as well as creating the plan to protect the forest from poachers and limit the expansion of farming. Keyword: Yearn Kantipalo, Forest Conservation, Forest Landscape, Amphoe Buachet, Surin Province